2021
DOI: 10.1016/j.molliq.2021.115456
|View full text |Cite
|
Sign up to set email alerts
|

On the swelling properties of pom-pom polymers in dilute solutions. Part 1: Symmetric case

Abstract: The paper continues our previous study of complex polymers with two branching points of functionalities f 1 and f 2 known as pom-pom molecules [1]. Here, we analyze the asymmetric case, when f 1 = f 2 . Applying both the analytical approach, based on direct polymer renormalization, and computer simulations, we obtained the quantitative estimates for the set of universal size and shape characteristics of molecule as well as its individual branches. The main attention is pointed towards the impact of asymmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…An expression for 𝐢 𝑔 is provided in the Appendix in expression A.1. In the case of 𝑓 1 = 𝑓 2 we recover our previous result for the symmetric case [8].…”
Section: Size Characteristicssupporting
confidence: 88%
See 4 more Smart Citations
“…An expression for 𝐢 𝑔 is provided in the Appendix in expression A.1. In the case of 𝑓 1 = 𝑓 2 we recover our previous result for the symmetric case [8].…”
Section: Size Characteristicssupporting
confidence: 88%
“…This number of branches was chosen to show the effect of asymmetry and to avoid the effect of crowdedness which has been studied in our previous work [21]. Two cases of the arm length, 𝑁 𝑓 = 8 and 𝑁 𝑓 = 16 were examined, similarly to the case of a symmetric pom-pom polymer [8], the results were found to agree well. In work [19] it was shown that the reduced density is coupled to the amplitude π‘Ž of a repulsive force in equation (3.3).…”
Section: Dissipative Particle Dynamics Simulationsmentioning
confidence: 99%
See 3 more Smart Citations